The Death of Competitive in Comparative Advantage: The Importance Analysis of Public Policy Case Study of Chicken Farming in Blitar Regency, East Java Province, Indonesia - Putri Dwi Maulina (Jurnal Ilmiah Mahasiswa FEB, 2013)
Transformation of public policy for chicken farming in Blitar Regency, East Java Province, Indonesia was very important. Blitar Regency was able to supply chicken’s eggs as many as 70% for province and 30% for national in 2010. But, reality showed that the farmers often got loss and they always were pressured by their partner. Focus of this paper is to describe what and why these conditions occur and to consider what policy which is needed to solve these problems. Results of this research showed that chicken farming in Blitar had comparative advantage which was able to export to other regions, but the competitiveness was still low. In terms of public policy, central and local government only supported the preliminary stages but they didn’t provide further regulation to protect the farmers from the exploitation of their partner and broker who made them be loss. Keywords: public policy, comparative advantage, competitive advantage, productivity, organic law